The effect of ethical leadership on service recovery performance: A moderated mediation model of organizational virtuousness and trait mindfulness - Ma, Ding; Wajid, Nauman; Anser, Muhammad Khalid; Anjum, Zafar-Uz-Zaman; Jia, Xiaoyun (Frontiers in Psychology, 2022)
In the present study, we first examined the relationship between ethical leadership and frontline employees' (FLEs) service recovery performance (SRP) and then tested the mediating role of organizational virtuousness in the relationship between ethical leadership and SRP in service contexts. Finally, we examined the moderating effect of FLE trait mindfulness on the direct relationship between ethical leadership and organizational virtuousness, as well as the indirect relationship between ethical leadership and SRP, via organizational virtuousness. Three-waved survey data collected from 273 supervisor-employee dyads in different service sector organizations supported our hypothesized relationships. In addition to important theoretical implications, the study carries useful practical implications, particularly for managers who are concerned about improving SRP in the service contexts.